Deep‐Blue Thiophene‐Based Steric Oligomers as a Low‐Threshold Laser Gain and Host Material. Issue 11 (17th April 2020) - Han, Yamin; Bai, Lubing; Xu, Man; An, Xiang; Wei, Chuanxin; Sun, Lili; Sun, Ning; Yu, Mengna; Zhang, He; Lin, Jinyi; Ou, Changjin; Xie, Linghai; et al.
Abstract: Thiophene‐based (Th‐based) derivatives have received wide attentions in organic optoelectronics due to their excellent and tuneable optoelectrical properties as well as chemical modification. However, the low photoluminescence quantum yield in solid state limits their application in solution‐processed light‐emitting optoelectronic devices, especially in organic lasers. Herein, a novel blue‐emitting steric Th‐based fluorophore (MC8‐Th) with excellent optical gain behavior for organic laser is reported. Interestingly, MC8‐Th neat film exhibits efficient exceptional deep‐blue amplified spontaneous emission (ASE) behavior with a remarkably low threshold of 6.0 µJ cm −2 and full‐width‐at‐half‐maximum value of 2.6 nm. Furthermore, random laser signals are also obtained with the lowest threshold of 4.1 µJ cm −2 when incorporating the compound into an inert polystyrene (PS) matrix. In addition, low threshold (16 µJ cm −2, fivefold lower than those of F8BT neat films) yellow–green ASE emission (560 nm) is achieved through Förster resonance energy transfer. Meanwhile, ultrafast transient absorption spectroscopy is deployed here to observe the single‐molecular excitonic behavior in solution and PS‐blend, intermolecular excited state in neat film, and efficient energy transfer in MC8‐Th:F8BT‐blend films. As far as known, MC8‐Th shows lower threshold ASE/lasing behavior for the Th‐based conjugated materials. Abstract : Deep‐blue thiophene‐based steric oligomer (MC8‐Th) is constructed for efficient deep‐blue organic lasers with an extremely low threshold of 6.0 and 3.2 µJ cm −2 based on the MC8‐Th neat and polystyrene‐blend films, which are extremely low amplified spontaneous emission (ASE)/lasing thresholds for thiophene‐based materials. Interestingly, five times reduction in ASE threshold to 16 µJ cm −2 is achieved for MC8‐Th/F8BT‐blend gain.